The question of influence of Gorky on Kuprin`s works (Eurasian Journal of Philology Science and Education, 2016)
This article deals with the problem of literature about what the impact of the Maxim Gorky on the works of young writer at the time A.Kuprin. The author touches the evolution of the writer’s work, focusing on the introduction in 1902 by M. Gorky, when published the first volume of Kuprin`s»Tales». The article concerns the fact that Gorky’s influence on the early work of Kuprin was so great that the heroes of novels «coward» and «horse-stealing» are considered as continuation of Gorky`s vagabonds. The article quotes Tolstoy that Kuprinis higher than Gorky and Andreeva, that «he had more talent than Gorky»; about the importance of conversations with Chekhov, when Chekhov as a writer was invited to live and write in Yalta. In the final part of the article highlights the dedication of the story «The Duel» to Gorky, when the writer confesses how much he had learned from him, and he is grateful to him for that.
Keywords: influence; author; literary connections; pathos; story; tradition; hero.